Acts of Oppression Behind the Implementation of Cultuurstelsel in the Dutch East Indies 1830-1870 - Pratama, Yogi (Swarnadwipa, 2025)
This research aims to describe the acts of fraud that occurred behind the implementation of cultuurstelsel in the Dutch East Indies in 1830-1870. Starting from the implementation of the cultuurstelsel policy by governor general Van De Bosch, the reasons for implementing the cultuurstelsel, the acts of oppression that occurred during its implementation up to the abolition of the cultuurstelsel policy in 1870. The research method uses historical or historical methods in the form of descriptive narrative through 4 stages of heuristics, source criticism, interpretation, and historiography (historical writing). Based on research results, the implementation of the cultuurstelsel policy has seen several acts of oppression against the people, one of which is through cultuurstelsel in the form of rewards given to plant supervisors as an incentive to exploit the people by blackmailing them in order to achieve set production targets. Village heads also often act arbitrarily in determining land, labor contracts, and payments that are not in accordance with production results and the workload given to the people. The impact of this policy is very detrimental to the people, causing hunger, poverty and the spread of infectious diseases due to the exploitation they experience. Criticism and protests against these practices attracted the attention of the Dutch parliament. Finally, in 1870, the cultuurstelsel was removed from the Dutch East Indies and replaced with liberal policies. This research provides insight into the acts of oppression behind the implementation of cultuurstelsel in the Dutch East Indies in 1830-1870.